2020
DOI: 10.1155/2020/3932569
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sphingosine Kinase-1 and Sphingosine-1-Phosphate Receptor-3 in Severe Plasmodium falciparum Malaria with Pulmonary Edema

Abstract: Pulmonary edema (PE) is a major cause of pulmonary manifestations of severe Plasmodium falciparum malaria and is usually associated with acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). The sphingosine kinase-1 (SphK-1)/sphingosine-1-phosphate receptor-3 (S1PR-3) pathway has recently been reported to affect the pathogenesis of lung injury, but the expression of these proteins in the lungs of severe P. falciparum malaria patients has not been investigated. The cellular expression of SphK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In addition, the current study demonstrated an increase in SphK1 in malaria-infected mice, which was consistent with previous reports on inflammatory conditions and cancer [ 9 , 14 , 15 , 46 48 ]. This finding may stem from inflammation-induced apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the current study demonstrated an increase in SphK1 in malaria-infected mice, which was consistent with previous reports on inflammatory conditions and cancer [ 9 , 14 , 15 , 46 48 ]. This finding may stem from inflammation-induced apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Synthesis of S1P is catalyzed by SphK1/2. Severe Plasmodium falciparum malaria causes lung edema and an increase in SphK1 in lung tissues [99], suggesting a role of the SphK1/S1P axis in lung edema. The effects of SphK1/2 on acute lung injury were examined using SphK1/2 deficient mice.…”
Section: Protective Role Of S1p In Experimental Acute Lung Injurymentioning
confidence: 99%
“…Over expression of both SPHK-1 and S1PR-3 proteins were observed in lung tissues of PE indicating their role in the pathogenesis of pulmonary complications in severe malaria. (Viriyavejakul and Punsawad, 2020) 10 Human Endothelial glycocalyx breakdown products, markers of endothelial dysfunction, parasite biomass, S1P and NO levels were compared between Indonesian adults with falciparum malaria (severe and moderately severe) and healthy control…”
Section: Human Erythrocytesmentioning
confidence: 99%
“…Further, the involvement of S1P receptors, specifically increased S1PR 3 concentration with mortality has been documented in acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) patients (Sun et al, 2012 ), yet another severe complication of falciparum malaria which ranges from 5 to 25% of adults and 29% of pregnant women (Taylor et al, 2012 ). Anticipating implication of circulating S1PR 3 as a potential biomarker of severity in malaria induced ARDS, when the expression of the Sphk1 and S1PR 3 proteins were investigated in malaria-associated ALI/ARDS, up-regulated expression of these were demonstrated in the lung tissues of experimental mice and human malaria patients (Punsawad and Viriyavejakul, 2019 ; Viriyavejakul and Punsawad, 2020 ). However, agreeing to evidence from previous studies (Finney et al, 2011 ; Punsawad and Viriyavejakul, 2017 ), plasma and lung tissues level of S1P was significantly less in malaria infected mice with ALI/ARDS) compared to non-ALI/ARDS and control (Punsawad and Viriyavejakul, 2019 ).…”
Section: S1p and Its Association With Malariamentioning
confidence: 99%